From Jerusalem to Timbuktu : a world tour of the spread of Christianity - Stiller, Brian (IVP Books, an imprint of InterVarsity Press, 2018)
What has led to the church's vibrant growth throughout the Global South? Brian Stiller identifies five key factors that have shaped the church, from a renewed openness to the move of the Holy Spirit to the empowerment of Indigenous leadership. Discover the surprising story of the global advance of the gospel. And be encouraged that Jesus' witness continues to the ends of the earth.